2012
DOI: 10.5333/kgfs.2012.32.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Forages on Growth Performance, Meat Production and Meat Quality of Hanwoo Steers : Meta-analysis

Abstract: In the present study, the effects of feeding different forage sources on the growth performance, meat production and meat quality of Hanwoo steers were evaluated using meta-analysis. In total 5 studies that were performed and published in the domestic journals in Korea were employed for the analysis. The results from nutritionally better quality roughage-based steers and rice straw-based steers in each study were assigned as a treatment and a control, respectively, and the mean difference between the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The highest among Q statistics was TG in blood, with high significance ( p < 0.0001). The significance of the Q statistic implies that the studies used to calculate the overall effect (the effect size of fixed and random effect models) do not share the same effect size with one another (Cho et al [ 70 ]). In this study, the Q statistics for all items were found to be significant ( p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest among Q statistics was TG in blood, with high significance ( p < 0.0001). The significance of the Q statistic implies that the studies used to calculate the overall effect (the effect size of fixed and random effect models) do not share the same effect size with one another (Cho et al [ 70 ]). In this study, the Q statistics for all items were found to be significant ( p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…The τ 2 value indicates the absolute value of heterogeneity, representing variance in true effect sizes [ 74 ]. In addition, liver TG showed the highest τ 2 value, which means that variance in the effectiveness of chitosan administration is great (Cho et al [ 70 ]).…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistical difference observed in carcass characteristics with different silages (p>0.05) for yield traits, including carcass weight, ribeye area, backfat thickness, and yield index. According to a meta-analysis on the effects of roughage quality on Hanwoo meat quality, the following traits can be affected: carcass weight, ribeye area, and yield index [ 27 ].…”
Section: Discussionmentioning
confidence: 99%